Capital Femoral Epiphyseal Extension May Confer Physeal Stability in Slipped Capital Femoral Epiphysis. Issue 3 (March 2019) - Morris, William Z.; Napora, Joshua K.; Conry, Keegan T.; Liu, Raymond W.
Abstract : Background: Factors including obesity and morphologic parameters around the hip that increase physeal stress are associated with an increased risk of slipped capital femoral epiphysis (SCFE). Recent evidence suggests that superior epiphyseal extension may confer stability to the physis and help protect against SCFE. The purpose of this study is to investigate the relationship between epiphyseal extension and SCFE using an age-matched and sex-matched cohort study. Methods: We generated 2 separate cohorts for comparison: 89 patients with unilateral SCFE and 89 healthy subjects with no evidence of hip disease or deformity. We utilized the anterior-posterior and lateral films of the hip to measure the Southwick angle and the epiphyseal extension ratio (EER), defined as the ratio of extension of the capital femoral epiphysis down the femoral neck relative to the diameter of the femoral head. We then compared these measurements between cohorts and in subgroup analysis based on slip stability and whether subjects progressed to a contralateral slip. Results: The SCFE cohort demonstrated a decreased superior epiphyseal extension ratio compared with control (superior EER 0.71 vs. 0.68, P =0.002). There was also a significant downward trend in superior EER from the control subjects (0.71±0.07) to the stable slips (0.69±0.06) to the unstable slips (0.65±0.04) with an overall difference between the groups ( P =0.001). Eighteen of 44 (41%) subjects with unilateral stable slips and at least 6 months of follow-up went on to develop SCFE of the contralateral limb. The subjects who developed contralateral slips were younger (11.6±1.2 vs. 12.7±1.4 y, P =0.008); however, there was no difference in superior or anterior epiphyseal extension ( P =0.75 and 0.23, respectively). There was no significant linear correlation between Southwick angle and superior or anterior EER ( r =0.13 and 0.17, respectively, P >0.05 for both). Conclusions: Increasing capital femoral epiphyseal extension may confer physeal stability in the setting of SCFE. We propose that this epiphyseal extension reflects an adaptive response to limit physeal stress and reduce the risk for progression to SCFE. Level of Evidence: Level III—prognostic study.